Analisis Faktor yang Memengaruhi Perencanaan Keuangan Pribadi di Surabaya - Dika Ananda Nur Laili (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
Personal financial planning regulates personal finance to achieve personal economic satisfaction and financial goals. The research intends to determine financial literacy, financial knowledge, financial attitude, gender, and financial awareness on personal financial planning. In this research, the respondents are Faculty Economics and Business Universitas Negeri Surabaya college students. This research uses the casualty research method with 146 respondents as the sample and uses snowball sampling acquired from online questionnaires. The data were analyzed with multiple linear regression and using SPSS 23. The research shows that financial literacy, financial knowledge, attitude, and awareness positively affect personal financial planning. Meanwhile, the variable gender does not affect personal financial planning. This research can educate college students to understand financial decisions, financial goals, and financial risks. Furthermore, they can realize the importance of saving and daily financial plans.